Trypanosoma brucei Co-opts NK Cells to Kill Splenic B2 B Cells. - Deborah Frenkel; Fengqiu Zhang; Patrick Guirnalda; Carole Haynes; Viki Bockstal; Magdalena Radwanska; Stefan Magez; Samuel J Black (PLoS Pathogens)
After infection with T. brucei AnTat 1.1, C57BL/6 mice lost splenic B2 B cells and lymphoid follicles, developed poor parasite-specific antibody responses, lost weight, became anemic and died with fulminating parasitemia within 35 days. In contrast, infected C57BL/6 mice lacking the cytotoxic granule pore-forming protein perforin (Prf1-/-) retained splenic B2 B cells and lymphoid follicles, developed high-titer antibody responses against many trypanosome polypeptides, rapidly suppressed parasitemia and did not develop anemia or lose weight for at least 60 days. Several lines of evidence show that T. brucei infection-induced splenic B cell depletion results from natural killer (NK) cell-mediated cytotoxicity: i) B2 B cells were depleted from the spleens of infected intact, T cell deficient (TCR-/-) and FcγRIIIa deficient (CD16-/-) C57BL/6 mice excluding a requirement for T cells, NKT cell, or antibody-dependent cell-mediated cytotoxicity; ii) administration of NK1.1 specific IgG2a (mAb PK136) but not irrelevant IgG2a (myeloma M9144) prevented infection-induced B cell depletion consistent with a requirement for NK cells; iii) splenic NK cells but not T cells or NKT cells degranulated in infected C57BL/6 mice co-incident with B cell depletion evidenced by increased surface expression of CD107a; iv) purified NK cells from naïve C57BL/6 mice killed purified splenic B cells from T. brucei infected but not uninfected mice in vitro indicating acquisition of an NK cell activating phenotype by the post-infection B cells; v) adoptively transferred C57BL/6 NK cells prevented infection-induced B cell population growth in infected Prf1-/- mice consistent with in vivo B cell killing; vi) degranulated NK cells in infected mice had altered gene and differentiation antigen expression and lost cytotoxic activity consistent with functional exhaustion, but increased in number as infection progressed indicating continued generation. We conclude that NK cells in T. brucei infected mice kill B cells, suppress humoral immunity and expedite early mortality.